How to get published in a scientific journal - Khatib, Alfi (2020)
Publication is necessary as requirement for graduation, promotion, to get reward/award, to be recognized, to disseminate knowledge, and communication among scientist. However, a good skill is required in order to produce an impactful scientific article in a good journal. This workshop aims to highlight an important aspect on writing a scientific article and to submit it to a scientific journal.